High-density lipoprotein cholesterol and cognitive impairment: A U-shaped relationship in China’s aging population - Fei Wang; Xiang Shang; Qiqi Yang; Zhuang Tao; Weimin Li; Meixia Wang; Fei Li (PLoS ONE, 2026)
This study investigated the association between high-density lipoprotein cholesterol (HDL-C) levels and the risk of cognitive disorders in older adults. Data were obtained from the 2011 Chinese Health and Retirement Longitudinal Study and included 7,509 participants. Cognitive function was assessed using a scale that measured episodic memory and mental status. Statistical analyses included multiple linear regression, restricted cubic splines, and threshold effect analysis to explore the relationship between HDL-C levels and cognitive scores. Compared with Q1 (<35 mg/dL), very high HDL-C was associated with lower cognitive scores (Q4: β = −0.622 [95% CI, −0.908 to −0.337]; Q5: β = −0.322 [−0.627 to −0.017]). A U-shaped association was observed, with a turning point at 67.43 mg/dL. Below the threshold, a 1-SD higher HDL-C was associated with a 0.08-SD higher cognitive score (β = +0.08; 95% CI, 0.06–0.11; p < 0.001), whereas above the threshold a 1-SD higher HDL-C was associated with a 0.07-SD lower score (β = −0.07; 95% CI, −0.14 to −0.01; p = 0.019). Therefore, the relationship between lipid profiles and cognitive health is nuanced and nonlinear. Understanding these complexities is crucial for developing strategies to maintain cognitive function in older adults.